A study of a wire–wireless hybrid NoC architecture with an energy-proportional multicast scheme for energy efficiency. (July 2015) - Dai, Peng; Chen, Jenhui; Zhao, Yiqiang; Lai, Yen-Han
Abstract: The efficiency of interconnect network-on-chip (NoC) design significantly affects the thermal and energy-consumption problems. The wireless interconnect NoC (WiNoC) design provides a promising NoC architecture for multicast in chip multiprocessor (CMP) as compared with fully wired NoC. However, wireless routers (WRs) cost a larger area size as well as larger energy consumption than wired routers do. In this paper, we study a 2-tier wire–wireless hybrid NoC (WHNoC) architecture in an ( NS ) -processing-element (PE) CMP where N PEs use wires to connect with a wireless-enabled hub forming a star topology subnet and S wireless-enabled hubs form a fully connected WiNoC, named sWHNoC. We first investigate the performance of slotted p -persistent carrier sense multiple access (CSMA) protocol on the fully connected WiNoC. To greatly reduce the energy consumption of WiNoC, we propose an energy-proportional multicast scheme (EMS) by using a power-gating (PG) technique to switch off non-member WRs during the period of multicast transmission. A comprehensive comparison of the star-ring WHNoC, the mesh-based WHNoC, and the proposed sWHNoC is studied. Detailed analyses of the energy consumption of sWHNoC are presented. The correctness of analysis is validated by using Orion 2.0 simulator. Based on our investigation, the sWHNoC with the slotted p -persistent CSMA and the EMS will significantly reduce the energy consumption as well as the transmission latency in CMP.